2017
DOI: 10.3390/ijms18051092
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Combination of Withaferin A and Sulforaphane Inhibits Epigenetic Machinery, Cellular Viability and Induces Apoptosis of Breast Cancer Cells

Abstract: With cancer often classified as a disease that has an important epigenetic component, natural compounds that have the ability to regulate the epigenome become ideal candidates for study. Humans have a complex diet, which illustrates the need to elucidate the mechanisms of interaction between these bioactive compounds in combination. The natural compounds withaferin A (WA), from the Indian winter cherry, and sulforaphane (SFN), from cruciferous vegetables, have numerous anti-cancer effects and some report their… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…HDAC expression also was downregulated at multiple levels, and a reduction in antiapoptotic BCL-2 and increase in proapoptotic Cancer May 15, 2019 BAX was observed. 43 Further study regarding the effect of this combination on the regulation of epigenetic mechanisms involved in breast cancer prevention demonstrated that it downregulated the level of cyclin D1 and CDK4, and pRB. In contrast, the level of E2F mRNA and the tumor suppressor p21 were increased independently of p53.…”
Section: Combination With Other Natural Bioactive Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…HDAC expression also was downregulated at multiple levels, and a reduction in antiapoptotic BCL-2 and increase in proapoptotic Cancer May 15, 2019 BAX was observed. 43 Further study regarding the effect of this combination on the regulation of epigenetic mechanisms involved in breast cancer prevention demonstrated that it downregulated the level of cyclin D1 and CDK4, and pRB. In contrast, the level of E2F mRNA and the tumor suppressor p21 were increased independently of p53.…”
Section: Combination With Other Natural Bioactive Compoundsmentioning
confidence: 99%
“…28 Combination therapy with chemotherapeutics may work in a synergistic or additive manner, lowering the therapeutic dosage of one agent and thereby reducing toxic effects. 5 Several chemotherapeutic drugs have been tested in combination with PIP, SFN, and TQ, as described below (the summarized mechanisms of action of the combinations are shown in Table 4 [8][9][10][11]16,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] ).…”
Section: Combination With Chemotherapeutic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies conducted by Meeran et al revealed that a diet containing compounds with HDAC and DNMT inhibitory activities altered the epigenome, resulting in the modulation of various aberrant epigenetics patterns in tumor‐related genes . Therefore, Paul et al decided to evaluate the effects deriving from the combination of genistein 38 and sulforaphane 39 (Combination E, Figure ) .…”
Section: The Mmt Approachmentioning
confidence: 99%
“…121 Previous studies conducted by Meeran et al 120 revealed that a diet containing compounds with HDAC and DNMT inhibitory activities altered the epigenome, resulting in the modulation of various aberrant epigenetics patterns in tumor-related genes. 75,122 Therefore, Paul et al decided to evaluate the effects deriving from the combination of genistein 38 and sulforaphane 39 (Combination E, Figure 3). 123 Genistein 38/sulforaphane 39 combination decreased the HDAC2 and HDAC3 expression both at protein and mRNA levels, downregulating KLF4, essential in stem cells formation, as well as hTERT that is known to be activated when KLF4 binds its promoter region.…”
mentioning
confidence: 99%